A representação de manifestantes e agentes públicos como atores sociais em textos sobre os protestos no Brasil em 2013 - Lima, Priscila de Oliveira Novais (2015)
This work is inserted in a convergence area among Translation Studies, Critical Discourse Analysis and Representation of Social Actors, as the representation of social actors in journalistic texts written in Portuguese and in English are analyzed. Texts about the demonstrations that took place in Brazil in June 2013, originally written in Portuguese and in English are analyzed, setting up what Tagnin (2004) considers a bilingual comparable corpus. The theoretical foundation used for the analysis is the Theory of Representation of Social Actors, introduced by van Leeuwen (1997), which is derived from the Systemic Functional Linguistics. The Theory of Representation of Social Actors introduces a sociosemantic inventory to investigate the representation of participants of social practices. To perform the analysis, the social actors who, somehow, have actively participated or supported the social practice known as Manifestations in Brazil are called Manifestantes; and the social actors who, somehow, have helped to contain this movement are called Agentes Públicos. Using the Corpus Linguistics tools, corpus has been annotated in order to identify how these social actors were excluded or included in the analyzed texts. The results indicate that in addition to making use of distinct linguistic elements to refer to the social actors in both languages, the texts analyzed in Portuguese and English seem to emphasize different cuts of the same social practice. This dissimilarity in the way of re-contextualizing the same event or social practice brings up questions about the discursive aspects regarding journalistic texts in the language pair analyzed in this work. From this analysis, it is pointed out how much and in which ways the different manners to re-contextualize the same event can build different meanings in the two linguistic systems.